Trade and Worker Deskilling - Rui Costa; Swati Dhingra; Stephen Machin (Institute of Labor Economics (IZA), 2019)
This paper presents new evidence on international trade and worker outcomes. It examines a big world event that produced an unprecedentedly large shock to the UK exchange rate. In the 24 hours in June 2016 during which the UK electorate unexpectedly voted to leave the European Union, the value of sterling plummeted. It recorded the biggest depreciation that has occurred in any of the world's four major currencies since the collapse of Bretton Woods. Exploiting this variation, the paper studies the impact of trade on wages and worker training. Wages and training fell for workers employed in sectors where the intermediate import price rose by more as a consequence of the sterling depreciation. Calibrating the estimated wage elasticity with respect to intermediate import prices to theory uncovers evidence of a production complementarity between workers and intermediate imports. This provides new direct evidence that, in the modern world of global value chains, it is changes in the cost of intermediate imports that act as a driver of the impact of globalization on worker welfare. The episode studied and the findings add to widely expressed, growing concerns about poor productivity performance relating to skills and to patterns of real wage stagnation that are plaguing contemporary labour markets.
Keywords: F14; F31; F66; J24; J31; 330; exchange rate depreciation; trade; wages; training; deskilling